A Mutation in the ANK2 Gene Causing ASD and a Review of the Literature - Lu Zhao; Zhi‐Dong Qiao; Yue‐Xin Jia; Jun‐Xian Fu; Tian‐Xia Li; Kai‐Ru Jia; Hong Zhao; Jin‐Ping Bao; Xiao‐Fan Yang; Hao Pan; Guang‐Lu Yang (Molecular Genetics & Genomic Medicine)
ABSTRACT Objective To investigate the clinical and genetic characteristics of patients with ANK2(HGNC:493)‐associated autism spectrum disorders (ASDs) and epilepsy (EP). Methods We identified a novel ANK2 variant in a patient with ASD and EP and summarized the clinical and genetic characteristics of ANK2 gene variants in this patient and those in previous reports. Results A novel nonsense variant, ANK2 (NM_001148.6):c.3007C>T/p.R1003* in exon 27, was identified in one patient. We described the clinical features and molecular genetics of this patient and previously reported patients. This was discovered at a follow‐up visit to the pediatric neurology department where genetic testing based on condition identified this rare genetic variant. He mainly presents with language delay, intellectual disability, limited learning, and communication skills, and later develops seizures, combined with common childhood neurological disorders such as hyperactivity, behavioral abnormalities, and even self‐injury. The patient cohort included 16 patients with a complex array of neurological disabilities: ASD (9 patients); EP (10 patients); ASD with EP (4 patients); intellectual disability and developmental delay (5 patients); poor language communication (11 patients); language and learning impairment (11 patients); anxiety/agitation mood disorder (6 patients); attention‐deficit/hyperactivity disorder (5 patients); cognitive, memory, and adaptability deficits (1 patient); tic disorder (1 patient); electrocardiogram and cardiac damage (1 patient); and abnormal electroencephalography (EEG) (9 patients). Conclusion For the first time, we identified a novel variant of the ANK2 gene in China, broadening the genetic spectrum of the ANK2 gene. ANK2 gene mutations can cause ASD, EP, ASD with EP, developmental delay and intellectual disability, poor language communication skills, language and learning disorders, anxiety/agitation mood disorder, and attention‐deficit/hyperactivity disorder. Clinical ASD, EP, common EP should consider the ANK2 gene mutation.